(untitled) - Gimpel, Jean (New York, 1976)
A close examination of the industrial life and institutions of the Middle Ages and of that inventiveness that laid the foundations for our present technologically oriented society.
Keywords: Lịch sử kinh tế,Economic history; Thời trung cổ, 500-1500,Medieval, 500-1500